Optimal policy: Which, where, and why - Bernardo Alves Furtado; Gustav Onofre Andre\~ao (Institute for Applied Economic Research (ipea), 2023)
The paper exploits a simulation environment and its output indicators to compare the performance of "ex-ante" policy instruments across housing and social welfare domains. We create a progressive score to contrast six single and mixed policy instruments against a no-policy baseline. The multiple simulation results include indicators for distinct instruments, cities, and policy goals. The exercise provides a counterfactual arena where we explore public investment trade-offs quantitatively and empirically - which constitutes a rare (usually impossible) policy practice. We demonstrate with data that policymakers may avoid incongruities by defining: i) which policy instrument; ii) to apply where; and iii) towards which goal (why). Results suggest that a mixed policy instrument evaluated by a comprehensive indicator performs better overall. However, optimal policy classification changes when considering different places or goals.
Keywords: R23; R31; C63; 330; Public policy; policy mix; policy design; policy instruments; agent-based model